Therapist written goodbye letters: evidence for therapeutic benefits in the treatment of anorexia nervosa. Issue 4 (17th July 2020) - Simmonds, Jess; Allen, Karina L.; O'Hara, Caitlin B.; Bartholdy, Savani; Renwick, Beth; Keyes, Alexandra; Lose, Anna; Kenyon, Martha; DeJong, Hannah; Broadbent, Hannah; Loomes, Rachel; McClelland, Jessica; et al.
Abstract: Background: Despite their use in clinical practice, there is little evidence to support the use of therapist written goodbye letters as therapeutic tools. However, preliminary evidence suggests that goodbye letters may have benefits in the treatment of anorexia nervosa (AN). Aims: This study aimed to examine whether therapist written goodbye letters were associated with improvements in body mass index (BMI) and eating disorder symptomology in patients with AN after treatment. Method: Participants were adults with AN ( n = 41) who received The Maudsley Model of Anorexia Treatment for Adults (MANTRA) in a clinical trial evaluating two AN out-patient treatments. As part of MANTRA, therapists wrote goodbye letters to patients. A rating scheme was developed to rate letters for structure and quality. Linear regression analyses were used to examine associations between goodbye letter scores and outcomes after treatment. Results: Higher quality letters and letters that adopted a more affirming stance were associated with greater improvements in BMI at 12 months. Neither the overall quality nor the style of goodbye letters were associated with improvements in BMI at 24 months or reductions in eating disorder symptomology at either 12 or 24 months. Conclusions: The results highlight the potential importance of paying attention to the overall quality of therapist written goodbye letters in the treatment of AN, and adopting an affirming stance.